IS IT REALLY KOCURIA KRISTINAE? - G. R. Rahim, Neha Gupta (Infectio, 2021)
Sir, We read with interest the case report “Endocarditis bacteriana por Kocuria kristinae en un paciente inmunocompetente. Reporte de caso” by S.M. Rojas Molina, et al1 . The authors described about the Kocuria kristinae endocarditis in an immunocompetent woman. We agree that Kocuria kristinae is a rare organism and endocarditis caused by this organism is worth mentioning. However, there are certain questionable points in the report which we would wish to highlight and which need clarification.